PERANAN MASJID DALAM MEMBENTUK KARAKTER AKHLAK MUSLIM MAHASISWA STSN - Budi Siswanto (Tadrib: Jurnal Pendidikan Agama Islam, 2019)
Mosque which literally means "place of prostration" (in prayer). Mosques are also known as Islamic centers, Islamic community centers or Muslim community centers. During Ramadan, Muslims spend a lot of time at the masjid, or mosque, for special prayers and community events. The mosque is a very strategic place in shaping the morals of Muslim societies. STSN students are a part of the community located in the Istiqomah mosque of Bumi Sanapati campus. The Istiqomah Mosque has various kinds of religious activities which are managed by student administrators and are intended specifically for STSN students. This research is a qualitative descriptive study conducted by reviewing the literature, observations, interviews and primary data collection through questionnaires to STSN students. The results of this study indicate that the Istiqomah mosque carried out activities carried out by STSN students and the activities of the Istiqomah mosque played a role in shaping the Muslim morals of STSN students. The measurement values ​​of Muslim moral characters of STSN students conducted by distributing questionnaires showed that 34.83% of students stated that they were very suitable, 53.95% of students stated appropriate, 9.93% of students expressed doubts and 1.28% of students stated that they were inappropriate . From the results of the questionnaire assessment shows the activities of the Istiqomah mosque have a role in shaping the moral character of STSN students in the form of morals towards Allah, towards fellow humans and morals towards the environment.